First report of tinea corporis caused by Arthroderma benhamiae in Brazil - de Freitas, Roseli Santos (Braz J Microbiol, 2019)
Arthroderma benhamiae is a zoophilic dermathophyte that can cause highly inflammatory tinea corporis and tinea capitis in humans. This is the first report of a patient with dermatophytosis caused by A. benhamiae in Brazil. The lesion was an erythematous, annular plaque on the lumbar region that appeared few weeks after playing with a street cat in a 19-month-old girl. Initial presumed diagnosis was tinea corporis caused by Microsporum canis. Topical treatments were ineffective and the patient required systemic treatment with griseofulvin. Mycological diagnosis was inconclusive: morphological differentiation between M. canis and Trichophyton benhamiae may be difficult, especially when the latter present yellow colonies. The etiological agent was identified only by ITS sequencing of the isolates aligned with reference strains to A. benhamiae. This report highlights the importance of ITS sequencing in the identification of isolates from some cases of dermatophytosis, because conventional morphological diagnosis may result in misdiagnosis of the agent and delay proper treatment.